2019
DOI: 10.1071/an18205
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the mechanism whereby dietary nicotinic acid increases the intramuscular fat content in finishing steers by RNA sequencing analysis

Abstract: In our previous study, we found that a higher dosage of nicotinic acid (NA) in the diet dramatically increases intramuscular fat (IMF) content and improves meat quality in finishing steers. We hypothesised that increased IMF results from the regulation of genes associated with adipogenesis. To address this hypothesis, RNA-seq was used to investigate gene-expression profiles of longissimus muscles from the same 16 cattle that were also used in our previous study and treated with or without dietary NA. Four cDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The MYH10 gene is a member of the myosin superfamily of protein-coding genes in cattle, humans, mice, chickens, sheep, and several other species. The MYH10 gene is associated with skeletal muscle in human (Mascarello et al, 2016), muscle characteristics in beef cattle (Yang et al, 2019) and pigs (Óvilo et al, 2014), and body size in sheep (Kominakis et al, 2017;Signer-Hasler et al, 2019). In Holstein cattle, the MYH10 gene is associated with milk production (Do et al, 2017) and body conformation traits (Abo-Ismail et al, 2017;Jiang et al, 2019), which is consistent with our findings.…”
Section: Major Qtl Detected On Bta19supporting
confidence: 89%
“…The MYH10 gene is a member of the myosin superfamily of protein-coding genes in cattle, humans, mice, chickens, sheep, and several other species. The MYH10 gene is associated with skeletal muscle in human (Mascarello et al, 2016), muscle characteristics in beef cattle (Yang et al, 2019) and pigs (Óvilo et al, 2014), and body size in sheep (Kominakis et al, 2017;Signer-Hasler et al, 2019). In Holstein cattle, the MYH10 gene is associated with milk production (Do et al, 2017) and body conformation traits (Abo-Ismail et al, 2017;Jiang et al, 2019), which is consistent with our findings.…”
Section: Major Qtl Detected On Bta19supporting
confidence: 89%
“…There were some ways to increase IMF content, for example, Sun et al (2020) suggested that the IMF deposition of sheep was promoted by mulberry leaves diets which may be related to the fact that mulberry leaf flavonoids can increase insulin levels in animals. Yang et al (2019) indicated a higher dosage of nicotinic acid dietary increased the IMF deposition by upregulating the expression of genes related to adipocyte differentiation, adipogenesis, and lipid and glucose metabolism based on transcriptomics. We found that dietary Lactobacillus supplementation could increase IMF of sheep by regulating lipid metabolism‐related pathways based on metabonomics, the mechanism of which will be discussed later.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis was used to map all DEGs to GO terms in the GO database. 2 The significance was calculated using a hypergeometric test by Yang ( 18 ).…”
Section: Methodsmentioning
confidence: 99%